Extending the concept of property to support the legal protection of digital resources / Wong Wai Wai - Wong, Wai Wai (2016)
The rapid advancement of information technology and World Wide Web has created many valuable and useful digital resources. As many of these digital resources are commonly, freely available over the internet, people pay little attention for its protection. The lack of legal recognition and acknowledgement of the significance; importance and the value of these digital resources have exposed them to misuse and abuse. There is a vacuum in law and gap in knowledge as to how these digital resources should be protected and be safeguarded accordingly.